2012
DOI: 10.1155/2012/578916
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Treatment of Shower Water Using a Pilot Scale Reactor

Abstract: Treatment of shower water deserves special consideration for reuse not only because of its low pollutant loading but also because it is produced in large quantities. In this study, a pilot scale study of photocatalytic degradation of impurities in real shower water was performed in a 31 L volume reactor using titanium dioxide as the photocatalyst. The reactor was operated in a continuous slurry recirculation mode. Several operational parameters were studied including the slurry initial pH, catalyst concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In the transition region, gas liquid interfacial area decreased and photocatalytic activity decreased from 64% at 20 L/min to be 41% at 35 L/min. The same result was obtained from Konsowa et al and Vishnu Pareek et al [36,37].…”
Section: The Effect Of Air Flowratesupporting
confidence: 89%
“…In the transition region, gas liquid interfacial area decreased and photocatalytic activity decreased from 64% at 20 L/min to be 41% at 35 L/min. The same result was obtained from Konsowa et al and Vishnu Pareek et al [36,37].…”
Section: The Effect Of Air Flowratesupporting
confidence: 89%
“…The excess active sites due to a high catalyst loading increased the rapid-rate reaction on the catalyst surface, which simultaneously resulted in shortening of the catalyst life span by coke formation caused by polymerization reaction. 56 In the present study, 1 wt% catalyst loading was observed to be optimal for the catalytic DO reaction. Fig.…”
Section: Optimization Studiesmentioning
confidence: 53%
“…The point of zero charge (pzc) of the TiO 2 Aeroxide P25 is reported to be at pH 6.5. Thus, the TiO 2 surface is positively charged in an acidic medium (pH < 6.5) and it is negatively charged in an alkaline medium (pH > 6.5), as is shown in Equations (12) and (13) [ 34 ]. When pH < pzc: TiOH + H + ↔ TiOH 2 + When pH > pzc: TiOH + OH − ↔ TiO − + H 2 O …”
Section: Resultsmentioning
confidence: 99%